Review of the Flexible Credit Line, the Precautionary and Liquidity Line, and the Rapid Financing Instrument : Specific Proposals. (Policy Papers; Policy Paper, 2014)
This annex provides the key considerations for establishing the qualification framework to access financing under the FCL and PLL, with a view to promoting a predictable and evenhanded qualification process.